(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
This article analyzes the issues of foreign labor migration, which has become an urgent problem today. Due to the demand of time, many of our compatriots have become foreign labor migrants and their social situation and problems have been thoroughly discussed. Also, the influence of population migration on the spirituality of young people, the nature of reforms in the field of migration in New Uzbekistan, the fact that migration is the cause of the transformation of the national spiritual value system established in our society, the existing problems in this area and the tasks necessary to solve them, in the future, researching the interaction of the spiritual environment and population migration in our country opinions about problems related to